Polymer‐Based Spherical Activated Carbons in Combination with TS‐1 as Efficient Epoxidation Catalysts1. Issue 9 (12th August 2015) - With, Patrick C.; Wilde, Nicole; Modrow, Antje; Fichtner, Sven; Böhringer, Bertram; Gläser, Roger
Abstract The heterogeneously catalyzed epoxidation of commercially available biodiesel with aqueous H2O2 as an oxidant was studied over composite catalysts consisting of microporous titanium silicalite‐1 (TS‐1) as reactive and polymer‐based spherical activated carbon (PBSAC) as sorptive component. The results are compared to that of a commercial TS‐1 catalyst. The polymer‐based spherical activated carbon was applied either as a support or as an exotemplate. In the composite catalyst, the active titanium sites are utilized four times more efficiently than in the commercial TS‐1.